Intraduodenal foreign body - Bortagaray, Carlos; Errandonea, Jorge (Cirugía del Uruguay, 1973)
A patient had carried for five years as introduodenal gauze roll which he had tollerated until recently when he began to suffer from digestive problems which led to exploratory surgery. The foreign body was extracted by enterotomy. Since no similar case was found in the bibliography consulted, we consider its presentation justified.